Study of Lipid Profile in Patients with Subclinical Hypothyroidism in Tertiary Center of Mid-Western Nepal - Sapkota, S.; Sah, B.; Malla, P. (Devdaha Medical Journal, 2024)
Introduction: Subclinical hypothyroidism (SCH), a common thyroid disorder, is differentiated by increased levels of thyroid-stimulating hormone (TSH) despite normal concentrations of free thyroid hormones. The aim of this study was to assess lipid abnormalities in patients with subclinical hypothyroidism and investigate its relationship with lipid profile and TSH. Methods: The cross-sectional study included 90 subclinical hypothyroidism individuals, from Nepalgunj Medical College and Teaching Hospital.  A blood sample was taken and sent to a laboratory for evaluation of the lipid profile Total Cholesterol (TC), Triglycerides (TG), High-Density Lipoprotein (HDL), Low-Density Lipoprotein (LDL), and Very Low-Density Lipoprotein (VLDL) and thyroid function tests (FT3, FT4, TSH). Results:  Participants had a mean age of 45.5 years and a TSH level of 5.9 ± 1.7 mIU/L. Lipid parameters showed elevated total cholesterol (210.7 ± 38.8 mg/dl), triglycerides (166.7 ± 1.9 mg/dl), LDL (116.3 ± 32.7 mg/dl), and VLDL (33.34 ± 4.85 mg/dl), along with low HDL (33.7 ± 6.8 mg/dl). TSH positively correlated with total cholesterol (r = 0.679), triglycerides (r = 0.879), and VLDL (r = 0.325), while HDL had a negative correlation (r = -0.4). FT3 and FT4 showed weaker negative correlations with lipid parameters.Conclusion: The study has concluded that the patients with subclinical hypothyroidism (SCH) exhibit significant gender-based differences in lipid profiles, with males showing higher levels of total cholesterol, triglycerides, LDL, and a higher Cholesterol/HDL ratio, along with significantly lower HDL levels.